PoV: An Efficient Voting-Based Consensus Algorithm for Consortium Blockchains - Li, Kejiao; Li, Hui; Wang, Han; An, Huiyao; Lu, Ping; Yi, Peng; Zhu, Fusheng (Frontiers in Blockchain, 2020)
The blockchain has a great vogue in recent years, and its core consensus algorithms also become the focus of research. At present, most of the research on consensus mechanisms are oriented to the public blockchain and based on existing consensus mechanisms or sophisticated distributed algorithms. Various application scenarios have been developed based on the consortium blockchain, while few researchers pay attention to customize consistency algorithms. Moreover, there is a trade-off between security and performance in designing consensus mechanisms. We propose a novel consensus algorithm called Proof of Vote (PoV), where the distributed nodes controlled by consortium members could reach consensus and come to a decentralized arbitration by voting. PoV separates the voting rights and bookkeeping rights with the essential idea of establishing different security identities for network nodes. Contrary to the third-party intermediary or uncontrollable public awareness, the production and verification of PoV blocks are decided by the voting results among the core consortium members. We theoretically prove that PoV blocks can reach transaction finality by only one confirmation. Compared with the total traffic complexity of BFT-based consensus, PoV has just that of O( ), which is a great improvement when the number of nodes is over 100.